PKM Pengolahan Sampah Organik dan Perilaku Bersih dan Sehat Kelompok Tani Wana Sari Di Desa Batur Utara, Kecamatan Kintamani, Bangli - Anak Agung Gede Indraningrat; Made Dharmesti Wijaya; I Wayan Sudiarta (Community Service Journal (CSJ), 2024)
The Wana Sari farmer group is a farmer group that carries out agricultural activities in North Batur Village, Kintamani District, Bangli. The agricultural activities carried out focus on plantation activities, especially fruit and vegetables. In carrying out farming activities, partners face daily problems in the health and agricultural sectors that require solutions and become the focus of PKM activities carried out by the service team. In the health sector, partner representatives said that the use of adequate personal protective equipment is still not uniform. Apart from that, partners also do not understand how to use drugs in everyday life, especially the aspect of careful movement using drugs (careful echo). In the agricultural aspect, partners produce quite a lot of organic agricultural waste, for example fruit and vegetable waste. So far, agricultural waste has not been processed into compost products because partners do not know how to make it. Partners also want to learn how to hatch BSF fruit fly larvae for further use as an effort to deal with organic waste and BSF maggots can be used as an alternative high-protein animal feed for chickens or fish. The implementation of PKM has been carried out with the service team providing outreach about careful monitoring and the importance of using PPE in farming activities. The service team also provides training on how to make compost from everyday plantation waste. Partners also received an explanation about maggot cultivation to be bred and used in daily life. In this activity, partners also received facilitation from the service team for each farmer member totaling 22 people in the form of a set of PPE, boots, medicine box and complete medicine, 10 grams of maggot larvae, maggot cultivation book, household scale composting bag along with biofad starter, bioactivator and gloves. Facilitation to farmer groups was also provided in the form of pressure measuring devices, waste chopping machines and molasses and biomi starters for large compost making. Comparison of pre and post-test shows an increase in partner scores of 30 points, which indicates an increase in partner understanding of the training provided. Monitoring and evaluation results show that partners are able to make compost independently, hatch BSF larvae to process organic waste, use PPE to carry out PHBS in farming activities.